Pediatric Neurology Briefs: Year in Review - John J Millichap (Pediatric Neurology Briefs Publishers, 2019)
In 2019, the mission of Pediatric Neurology Briefs (PNB) remains the same: "PNB is a continuing education service designed to expedite and facilitate the review of current scientific research and advances in child neurology and related subjects."